Regularização fundiária em áreas de várzeas da União no Estado do Pará: população extrativista e o acesso à cidadania no município de Muaná/PA no período de 2008 a 2014 - SILVA, Lélio Costa da (Universidade Federal do Pará, 2024)
Recognizing the right to use and occupy public areas of the Union for riverside populations in the Amazon region of Pará is a challenge. In this study, the issue of Land Regularization in floodplain areas of the Union is presented, and the management arrangement elaborated by the author and adopted and applied by the Union Heritage aiming at solving the problem of promoting access to citizenship with the riverside extractive population. It is presented as a case study, the impact of using the public management instrument in promoting land tenure regularization in floodplain areas along with traditional riverside communities in the Municipality of Muaná. This way of working land title regularization in floodplain areas is innovative, considering that in addition to social benefits, it is strictly related to the principles of sustainable development. This innovative management perspective comes from the use of the TAUS - Term of Authorization for Sustainable Use, which aims to guarantee the security of land tenure, ensuring that the property's socio-environmental function is fulfilled, considering organizational, political and economic aspects. The target audience are the riverside populations occupying the floodplain areas of federal rivers and islands where the influence of the tides is felt, as they are in the federal public domain. The legal basis used to implement this modality of public policy expressed in Ordinance No. 89/2010 which defined the management arrangement called Sustainable Use Authorization Term (TAUS). With the application of this term, the security of the possessions and occupations of the areas is guaranteed. This innovation had its genesis in the State of Pará from the demands of riverine families, who were under pressure from the "bosses" to accept and be submitted to the socalled "meação", which is a debasement relationship, where half of what they produced were forced to deliver to these “alleged owners”. In this secular framework, no family could access public credit, they found it difficult to reach social security rights, they could not prove their residence, in addition to the difficulty in obtaining environmental licensing for their rural activities. Thus, they could not prove residence either, as they did not have SPU/PA recognition until then. The exploratory and qualitative research showed that the implementation of the pilot project in the Municipality of Muaná-PA helped riverine communities in accessing citizenship, as it guaranteed land tenure security, access to credit (PRONAF), to social security benefits, environmental licensing, proof of residence and closed-end insurance. In the field, the research obtained several reports of the “liberation” of the target population of the action, since all those who accessed public policy stopped “giving half” to those who claimed to be owners of public lands. Therefore, the management arrangement proved to be important, effective and, above all, innovative. The experience provided subsidies for the application of TAUS in other municipalities in Pará, similar to those of the pilot experiment, as a way to improve and strengthen public policy.